2014
DOI: 10.1111/scs.12141
|View full text |Cite
|
Sign up to set email alerts
|

‘You put it all together’ – families' evaluation of participating in Family Health Conversations

Abstract: Family Health Conversations should be offered as a part of standard care shortly after diagnosis and at various transitions in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 38 publications
7
93
1
3
Order By: Relevance
“…Research into FamHc shows positive impact for families [19-22, 30-32]. Based on the increased evidence in the literature on positive outcomes of paying attention to families in health care, FamHC may facilitate building a trusting relationship with families that have a family member living in a residential home.…”
Section: Introductionmentioning
confidence: 99%
“…Research into FamHc shows positive impact for families [19-22, 30-32]. Based on the increased evidence in the literature on positive outcomes of paying attention to families in health care, FamHC may facilitate building a trusting relationship with families that have a family member living in a residential home.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that families experience a positive impact from participating in family health conversations and the 15-Minute Family Interviews in other contexts, for example, when a family member experiences chronic illness, cardiac and ischemic illness, depression or childhood cancer (Bell, 2015;Benzein et al, 2015;Östlund & Persson, 2014). This suggests that more empirical studies are needed in the context of families where a family member is diagnosed with breast cancer.…”
Section: The Families' Need For Supportmentioning
confidence: 99%
“…This is further emphasised by the number of women and families afflicted by breast cancer and their unmet need of support John et al, 2013). Moreover, the positive impact previous research has shown in families participating in family health conversations (FamHC) in other contexts, for example, when a family member experienced chronic illness, cardiac and ischemic illness, depression or childhood cancer (Bell, 2015;Benzein et al, 2015;Östlund & Persson, 2014), points to the importance of empirical studies involving the whole family.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations